Ulayat Rights on Presepective Customary Law - Arrahman, Nicolas (Universitas Negeri Semarang, 2019)
The implementation of Customary Law in Customary Law is increasingly critical, in the phenomenon of customary law, Ulayat Rights as stipulated in the UUPA Article 3 states